STUDI KASUS MINAT MEMBACA BUKU PADA MAHASISWA PGSD UWGM SAMARINDA - Siska Oktaviani; Nurul Hikmah (Universitas Negeri Medan, 2020)
This study aims to determine the condition of interest in reading books in PGSD UWGM final semester students who are in the process of writing a thesis. This type of research is a qualitative study using a case study approach. The research site is in UWGM Samarinda Campus located at KH. Wahid Hasyim No. 28, Samarinda Utara District,Kaltim Province. Data sources were obtained from students and data from the library and UWGM environment. Data collection techniques consist of interviews, observation and documentation. Data analysis techniques are done through data reduction, data display and conclusion drawing/verification. Data validity was also tested using triangulation techniques, namely triangulation techniques. From the results of interviews, observations and documentation obtained a description that by writing a thesis can generate interest in reading students because by reading, students can obtain references and information needed in writing a thesis.Keywords : Interest; Reading; Books; Students